Contrasting NPQ dynamics and xanthophyll cycling in a motile and a non‐motile intertidal benthic diatom. (20th March 2017) - Blommaert, Lander; Huysman, Marie J. J.; Vyverman, Wim; Lavaud, Johann; Sabbe, Koen
Abstract: Diatoms living in intertidal sediments have to be able to rapidly adjust photosynthesis in response to often pronounced changes in light intensity during tidal cycles and changes in weather conditions. Strategies to deal with oversaturating light conditions, however, differ between growth forms. Motile epipelic diatoms can migrate to more optimal light conditions. In contrast, non‐motile epipsammic diatoms appear to mainly rely on higher Non‐Photochemical Quenching (NPQ) of chlorophyll a fluorescence to dissipate excess light energy, and this has been related to a larger pool of xanthophyll cycle (XC) pigments. We studied the effect of 1 h high Photosynthetically Available Radiation (PAR) (2000 μmol photons m −2 s −1 ) on the kinetics of the xanthophyll cycle and NPQ in both a motile diatom ( Seminavis robusta ) and a non‐motile diatom ( Opephora guenter‐grassii ) in an experimental set‐up which did not allow for vertical migration. O. guenter‐grassii could rapidly switch NPQ on and off by relying on fast XC kinetics. This species also demonstrated high de novo synthesis of xanthophylls within a relatively short period of time (1 h), including significant amounts of zeaxanthin, a feature not observed before in other diatoms. In contrast, S. robusta showed slower NPQ and associated XC kinetics, partly relying on NPQ conferred by de novo synthetized diatoxanthin molecules and synthesis of Light‐Harvesting Complex X (LHCX) isoforms. Part of this observed NPQ increase, however, is sustained quenching (NPQs). Our data illustrate the high and diverse adaptive capacity of microalgal growth forms to maximize photosynthesis in dynamic light environments.